2005
DOI: 10.1099/jmm.0.46036-0
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacterium indologenes bacteraemia in a diabetic child

Abstract: Chryseobacterium indologenes is a non-fermentative Gram-negative bacillus that is a rare pathogen in humans. Its occurrence in diabetic children has not been previously reported. In this report, a case is described of C. indologenes bacteraemia possibly associated with the use of a peripheral venous catheter. A 2-year-old boy with type I diabetes mellitus was admitted due to a coma caused by cerebral oedema and was successfully treated for his neurological condition but presented on the tenth day after admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Appropriate antimicrobial treatment is required for bacteremia and other infections caused by C. indologenes in debilitated or immunosuppressed, individuals because of intrinsic antimicrobial resistance to penicillins, cephalosporins, aztreonam, carbapenems, chloramphenicol, and aminoglycosides chosen empirically to treat such serious Gram-negative infections. [12391011] In our case, uncontrolled diabetes mellitus was a risk factor for C. indologenes septicemia. With the worldwide occurrence, increase and rate of dissemination of bla NDM-1 , early detection is critical.…”
Section: Discussionmentioning
confidence: 56%
“…Appropriate antimicrobial treatment is required for bacteremia and other infections caused by C. indologenes in debilitated or immunosuppressed, individuals because of intrinsic antimicrobial resistance to penicillins, cephalosporins, aztreonam, carbapenems, chloramphenicol, and aminoglycosides chosen empirically to treat such serious Gram-negative infections. [12391011] In our case, uncontrolled diabetes mellitus was a risk factor for C. indologenes septicemia. With the worldwide occurrence, increase and rate of dissemination of bla NDM-1 , early detection is critical.…”
Section: Discussionmentioning
confidence: 56%
“…The one-year-old boy with burns developed an adult respiratory syndrome and died despite antimicrobial treatment; the other two patients recovered after three days of treatment. Cascio et al [11] reported on a two-year-old boy with type 1 diabetes mellitus who developed bacteremia. The only medical device present was a peripheral catheter.…”
Section: Discussionmentioning
confidence: 99%
“…indologenes typically exhibits resistance to multiple antibiotics (2,4,6). The species is naturally resistant to aminoglycosides and possesses chromosomal metallo-beta-lactamases.…”
mentioning
confidence: 99%